Work-family conflict in times of crisis: The moderating roles of self-efficacy and time-based spousal support during pandemic-induced remote work - Selda Coşkuner Aktaş (PLoS ONE, 2026)
The COVID-19 pandemic accelerated the global transition to remote work, requiring working parents to rapidly adapt to home-based arrangements. As work and family boundaries became increasingly blurred, concerns regarding work–family conflict (WFC) intensified. Drawing on Conservation of Resources (COR) Theory, Social Cognitive Theory (SCT), and Asymmetric Boundary Permeability Theory, the present study examined the relationships among time-based spousal support, self-efficacy, work- and family-related time demands, and WFC. Data were collected online from 211 working parents in dual-earner families engaged in pandemic-induced remote work. An a priori power analysis confirmed that the sample size was sufficient to detect medium effects. Results indicate that work-to-family conflict was higher than family-to-work conflict. While work- and family-related time demands were not directly associated with conflict, time-based spousal support moderated the relationship between work-related time demand and work-to-family conflict. Self-efficacy did not moderate time-demand relationships but was directly associated with lower levels of both work-to-family and family-to-work conflict. These results highlight the significance of contextual and personal resources in shaping work–family dynamics under crisis-driven and externally imposed work arrangements.